Comparative analysis of shale pore size characterization methods. (17th July 2020) - Yang, Xiaoguang; Guo, Shaobin
Abstract: The pore size distribution of four shale samples were characterized by and compared between CO2 adsorption, N2 adsorption, MIP and NMR. The results show that CO2 adsorption has an absolute advantage for characterization of pores smaller than 2 nm. N2 adsorption is reliable for 2–50 nm pore characterization and is superior to NMR in the 2–10 nm range. NMR has advantages for 10–100 nm pore characterization, and MIP has advantages for characterization of pores larger than 100 nm. NMR offers the widest range of observations, and order of the maximum resolution of these methods is CO2 adsorption > N2 adsorption > NMR > MIP.